2006
DOI: 10.1038/ncb1488
|View full text |Cite
|
Sign up to set email alerts
|

Control of Rad52 recombination activity by double-strand break-induced SUMO modification

Abstract: Homologous recombination is essential for genetic exchange, meiosis and error-free repair of double-strand breaks. Central to this process is Rad52, a conserved homo-oligomeric ring-shaped protein, which mediates the exchange of the early recombination factor RPA by Rad51 and promotes strand annealing. Here, we report that Rad52 of Saccharomyces cerevisiae is modified by the ubiquitin-like protein SUMO, primarily at two sites that flank the conserved Rad52 domain. Sumoylation is induced on DNA damage and trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
190
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(205 citation statements)
references
References 30 publications
13
190
2
Order By: Relevance
“…Moreover, SUMO is implicated in the maintenance of rDNA stability by suppressing illegitimate recombination among the yeast rDNA repeats [22]. Consistent with this widespread effect on genomic integrity, it was found that many other proteins involved in DNA repair are sumoylated, notably PCNA, Rad52, Rfa1, Rfa2, Sgs1 helicase, as well as its human homologues, BLM and WRN [23][24][25][26][27][28]. Many of these proteins are found either transiently or stably associated with PML-NBs in mammalian cells in response to DNA damage (reviewed in [20]).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, SUMO is implicated in the maintenance of rDNA stability by suppressing illegitimate recombination among the yeast rDNA repeats [22]. Consistent with this widespread effect on genomic integrity, it was found that many other proteins involved in DNA repair are sumoylated, notably PCNA, Rad52, Rfa1, Rfa2, Sgs1 helicase, as well as its human homologues, BLM and WRN [23][24][25][26][27][28]. Many of these proteins are found either transiently or stably associated with PML-NBs in mammalian cells in response to DNA damage (reviewed in [20]).…”
Section: Introductionmentioning
confidence: 61%
“…Mutations in genes involved in the SUMO pathway, such as Ubc9, Mms21, Ulp1, Slx5 and Slx8, render cells sensitive to DNA damage, and many proteins involved in the maintenance of genome stability have been shown to become sumoylated during the damage response [23][24][25][26][27][28]. Specifically, it has been shown that the SUMO pathway plays an important role in homologous recombination and the resumption of stalled/collapsed replication forks [27,[36][37][38].…”
Section: Dna Repair and Sumo In Yeastmentioning
confidence: 99%
“…Prolonged Rad51 association with DSB would eventually initiate BIR with other chromosomes to produce a translocation event. Intriguingly, the Rad52 protein and its S. pombe homolog Rad22 protein are sumoylated [43,70]. Although it is still unclear whether the sumoylation of Rad52 affects HR efficiency, it could at least affect the kinetics of the removal of Rad51 from DSB.…”
Section: Discussionmentioning
confidence: 99%
“…The Rad52 protein is sumoylated largely by Siz2 [43] and PCNA sumoylation by Siz1 is important to promote GCR [13]. We asked whether GCRs enhanced by the smc6-9 mutation could be affected by the siz1 or siz2 mutation ( Table 4).…”
Section: Translocations Produced In the Smc6-9 Strain Are Dependent Omentioning
confidence: 99%
“…Among these key pathways, Ubls regulate DNA repair and chromosome segregation mechanisms (Tanaka et al, 1999;Gill, 2004;Nacerddine et al, 2005;Ulrich, 2005). For example, the DNA homologous recombination repair (HRR) factor RAD52 is sumoylated in both yeast and mammals (Ho et al, 2001;Sacher et al, 2006). In budding yeast, Rad52 sumoylation affects both its stability and the outcome of Rad52-dependent HRR (Sacher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%